PENERAPAN SISTEM PENGENDALIAN INTERN PADA PT BANK PERKREDITAN RAKYAT (BPR) KUDAMAS SENTOSA - Hamzah, Arga Sepdrian (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this study was yo analyze the internal control system of channeling credit rating in order to runs effectively and efficiently on PT BPR Kudanas Sentosa. This study uses descriptive analysis. Based on this research PT BPR Kudamas Sentosa need special attention system of internal control, especially for the provision of credit. With asset quality reports which showed that the level of NPL (Non Performing Loan) at PT BPR Kudamas Sentosa in 2011 amounted to 3.71% and by 3.09% in 2012, so there is still a risk of bad debts or unpaid. Therefore, based on the result obtained from thistles study, the management of PT BPR Kudamas Sentosa is expected to be more selective in the level of serviced and procedures to focus on doing the scheduling of training to getting more effective results in increase knowledge in the field of credit.Keywords: Internal Control System, Productive Assets Quality, Record Procedure and Competence System as well as The Healthy Practical.